Core–shell gold nanorod@mesoporous-MOF heterostructures for combinational phototherapy. Issue 1 (18th December 2020) - Zhou, Zehao; Zhao, Jian; Di, Zhenghan; Liu, Bei; Li, Zhaohui; Wu, Xuemin; Li, Lele
Abstract : A core–shell heterostructure consisting of plasmonic gold nanorods and porphyrinic metal–organic frameworks is synthesized as a promising platform to combine photodynamic therapy and photothermal therapy for enhanced tumor treatment. Abstract : Despite the increasing usage of porphyrinic metal–organic frameworks (MOFs) for combination therapy, the controlled encapsulation of inorganic nanoparticle-based therapeutics into such MOFs with specific structures has remained a major obstacle for improved tumor therapy. Here, we report the synthesis of a mesoporous MOF shell on the surface of gold nanorods (AuNRs), wherein a single AuNR is captured individually in single-crystalline MOFs with a controlled crystallographic orientation, for combinational phototherapy against solid tumors. The core–shell heterostructures have the benefits of a mesoporous structure and photoinduced singlet oxygen generation behavior characterized by the porphyrinic MOF shell, together with the plasmonic photothermal conversion characteristic of AuNRs. We demonstrated that the AuNR@MOF nanoplatform enables an efficient tumor treatment strategy by combining photodynamic therapy and photothermal therapy. We should emphasize that such systems could have applications beyond the field of cancer therapy, like plasmonic harvesting of light energy to induce and accelerate catalytic reactions within MOFs and multifunctional nanocarriers for agricultural formulations.